Walkability Index Analysis on Pedestrian Facilities : Analisis Indeks Kelayakan Berjalan (Walkability Index) Pada Fasilitas Pejalan Kaki - Sopilawati, Rahma; Sulistyorini, Rahayu; Karami, Muhammad; Purba, Aleksander; Afriani, Lusmeilia (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Ryacudu Street in Sukarame District, Bandar Lampung City is the main route connecting the city center with the Trans Sumatra Toll Road. However, the design, provision of facilities, and maintenance of sidewalks along this road do not support optimal walking feasibility. Problems found include uneven sidewalk surfaces, discontinuous designs, many physical obstacles, and minimal supporting facilities. This study aims to analyze the Walkability Index on the Ryacudu Street sidewalk using nine parameters from the Global Walkability Index (GWI) approach. The results of the analysis show that the walkability value is in the range of 50–69, which is included in the “Waiting to Walk” category. This means that some pedestrian facilities can still be used, but are not optimal in terms of comfort, safety, security, and accessibility. Therefore, improvements are needed in the physical arrangement of sidewalks, provision of facilities, public space management policies, and enforcement of pedestrian space utilization regulations. This analysis provides strategic information on areas that need to be improved based on the value of each parameter analyzed.